A BIDIRECTIONAL ANGLO-GERMAN COMPARISON OF CONSIDERATION IN CONTRACT LAW. Issue 1 (January 2023) - Ungerer, Johannes
Abstract: This article explores the concept of consideration in contract law from a comparative perspective, looking at how English law and German law distinguish bargains from gifts. Contrary to the orthodoxy that consideration is unique to Common Law and absent from Civil Law, the bidirectional analysis in this article shows how English law and German law can be understood to fulfil a comparable function and can thus inform and benefit each other. The sophisticated English doctrine can be used to refine the rather imprecise German definition of gifts, whilst the understanding of English authorities can profit from reflecting inversely on the criterion of gratuitousness in German law.